Second harmonic generation imaging of head and neck squamous cell carcinoma - Stocker, Magdalena; Baumeister, Philipp; Canis, Martin; Vogel, Martin; Gires, Olivier (Frontiers in Imaging, 2023)
We assessed post-surgical human head and neck squamous cell carcinomas (HNSCC) and healthy tissue (n=10 each) via HHG (higher harmonic generation) imaging to differentiate healthy from tumor tissue.Qualitative imaging analysis compared collagen fibrils detected via immunohistology and SHG (second harmonic generation). Quantitative analysis measured the forward to backward intensity ratio (fSHG/bSHG) of SHG images. Assessments of the tissue samples demonstrated a structural difference of collagen matrix organization from healthy to malignant tissue. Healthy tissue was characterized by a high f/b ratio, describing highly organized tissue, whereas a low f/b ratio was observed in malignant tissue, indicative of reduced organization. Thus, HHG provides broad possibilities to analyze extracellular changes in diseased tissue, such as solid tumors.